2022
DOI: 10.1007/s12325-022-02099-0
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Radioembolization Versus Atezolizumab–Bevacizumab in Unresectable Hepatocellular Carcinoma: A Matching-Adjusted Indirect Comparison of Time to Deterioration in Quality of Life

Abstract: Introduction: Given the relatively short life expectancy of patients with hepatocellular carcinoma (HCC), quality of life (QOL) plays a significant role in treatment selection. This analysis aimed to compare time to deterioration (TTD) in QOL with transarterial radioembolization (TARE) and atezolizumab-bevacizumab, as well as sorafenib, in advanced and unresectable HCC.Methods: Patient-level data from SARAH (TARE using SIR-Spheres Ò Y-90 resin microspheres [SIR-Spheres] versus sorafenib) and aggregate data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Further multivariate regression analysis has elucidated pivotal factors influencing fatigue in liver cancer patients post-TAE, including marital status, presence of family members, and age[ 17 , 18 ]. Consistent with prior research, our study reveals that younger patients are more susceptible to experiencing fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Further multivariate regression analysis has elucidated pivotal factors influencing fatigue in liver cancer patients post-TAE, including marital status, presence of family members, and age[ 17 , 18 ]. Consistent with prior research, our study reveals that younger patients are more susceptible to experiencing fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to sorafenib, better tolerability has also been reported for TARE with fewer adverse events and a higher quality of life [11,12]. In fact, recently, an indirect comparison between patients in the SARAH and IMbrave150 trial has shown similar time to deterioration of quality of life [18]. With reports showing a similar safety profile, we aimed to identify patients who would benefit from TARE or atezolizumab/bevacizumab and improve individual treatment allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells play a critical role in regulating cardiovascular functions, as they are ubiquitously found in the lining of blood vessels. Endothelial cell dysfunction after TBI leads to dysregulation of the cardiovascular system, manifesting as volatile blood pressure, electrocardiogram changes, arrhythmias, and poor cardiac function (52)(53)(54)(55)(56)(57)(58)(59).…”
Section: Cardiovascularmentioning
confidence: 99%